Welfare impact of improved maize varieties adoption among smallholder farmers in Amuru district of Horo Guduru Wollega, Ethiopia - Gemechis Merga; Million Sileshi; Fresenbet Zeleke (Cogent Economics & Finance, 2023)
Government policy strategies, particularly in sub-Saharan Africa (SSA), are aimed at increasing agricultural productivity, which could contribute to improve household welfare. Hence, understanding smallholder farmers' low and variable crop yields has been a central research and policy priority in addressing food security. Likewise, the purpose of this study was to assess the impact of adopting improved maize varieties on productivity and food insecurity in Amuru district of Horo Guduru Wollega, Ethiopia. The study utilized cross-sectional household data collected in 2020/2021 from 263 randomly selected sample households. The probit model's findings indicate that factors that positively influenced households' adoption of the improved maize varieties included the household head's education level, the amount of livestock owned, access to credit, access to training, farm size, access to extension agents, and access to information from farmers associations, while factors that negatively influenced adoption included family size and market distance. The endogenous treatment effect model's findings also showed that IMV adoptions considerably improve smallholder farmers' welfare by lowering food insecurity and raising their average calorie intake and net crop values. Thus, it is advised that governments and other interested institutions should promote the adoption of improved maize varieties on a larger scale in order to boost maize yield and lower rural household food insecurity.
Keywords: 330; Adoption; Endogenous Switching Regression; Food Security; Impact; Improved Maize Varieties